WAIS-IV Performance in Patients With Schizophrenia. Issue 6 (June 2019) - Fuentes-Durá, Inmaculada; Ruiz, Juan Carlos; Dasí, Carmen; Navarro, Marisa; Blasco, Pilar; Tomás, Pilar
Abstract : Abstract: Wechsler Adult Intelligence Scale (WAIS) is one of the most widely used instruments to measure cognitive functioning. The aims of this study were 1) to obtain the cognitive profile of Spanish patients with schizophrenia on the WAIS-IV; 2) to compare their profile to the profile of a healthy control group; and 3) to compare the cognitive profile of patients with schizophrenia to the performance observed in two separate previous studies in Canada and China. A sample of 99 outpatients and 99 healthy control participants, matched on age, sex, and educational level, were measured using the WAIS-IV, including 10 core subtests, 4 indices, and 2 general intelligence scores, to obtain their cognitive profile. Results showed that only the performance on the Verbal Comprehension Index and its subtests was similar in the patient and control groups. This pattern of cognitive impairment was similar to the pattern reported in the Canadian and Chinese studies.